Patient and healthcare provider experiences of hepatitis C treatment with direct-acting antivirals in Rwanda: a qualitative exploration of barriers and facilitators - Janvier Serumondo; Michael J. Penkunas; Julienne Niyikora; Alida Ngwije; Athanase Kiromera; Emmanuel Musabeyezu; Justine Umutesi; Sabine Umuraza; Gentille Musengimana; Sabin Nsanzimana (BMC, 2020)
Abstract Background Direct-acting antivirals (DAAs) are increasingly accessible to patients with hepatitis C (HCV) worldwide and are being introduced through national health systems in sub-Saharan Africa. DAAs are highly efficacious when tested in controlled trials, yet patients treated outside of study settings often encounter challenges in completing the full treatment and follow-up sequence. Little information is available on the influences of successful DAA implementation in sub-Saharan Africa. This qualitative study explored the individual- and system-level barriers and enablers of DAA treatment in Rwanda between March 2015 and November 2017. Methods Face-to-face interviews were conducted with 39 patients who initiated care at one of four referral hospitals initially offering DAAs. Ten healthcare providers who managed HCV treatment participated in face-to-face interviews to examine system-level barriers and facilitators. Interview data were analyzed using a general inductive approach in alignment with the a priori objective of identifying barriers and facilitators of HCV care. Results Barriers to successful treatment included patients' lack of knowledge surrounding HCV and its treatment; financial burdens associated with paying for medication, laboratory testing, and transportation; the cumbersome nature of the care pathway; the relative inaccessibility of diagnostics technology; and heavy workloads of healthcare providers accompanied by a need for additional HCV-specific training. Patients and healthcare providers were highly aligned on individual- and system-level barriers to care. The positive patient-provider relationship, strong support from community and family members, lack of stigma, and mild side effect profile of DAAs all positively influenced patients' engagement in treatment. Conclusions Several interrelated factors acted as barriers and facilitators to DAA treatment in Rwanda. Patients' and healthcare providers' perceptions were in agreement, suggesting that the impeding and enabling factors were well understood by both groups. These results can be used to enact evidence-informed interventions to help maximize the impact of DAAs as Rwanda moves towards HCV elimination.